Accuracy of Bone Measurements in the Vicinity of Titanium Implants in CBCT Data Sets: A Comparison of Radiological and Histological Findings in Minipigs. (17th July 2017) - Gröbe, Alexander; Semmusch, Jan; Schöllchen, Maximilian; Hanken, Henning; Hahn, Michael; Eichhorn, Wolfgang; Schön, Gerhard; Jung, Ole; Stein, Jamal M.; Reitmeier, Aline; Heiland, Max; Smeets, Ralf; et al.
Abstract : Purpose . The aim of this animal study was the determination of accuracy of bone measurements in CBCT (cone-beam computed tomography) in close proximity to titanium implants. Material and Methods . Titanium implants were inserted in eight Göttingen minipigs. 60 implants were evaluated histologically in ground section specimen and radiologically in CBCT in regard to thickness of the buccal bone. With random intercept models, the difference of histologic measurements and CBCT measurements of bone thickness was calculated. Results . The mean histological thickness of the buccal bone was 5.09 mm (CI 4.11–6.08 mm). The four raters measured slightly less bone in CBCT than it was found in histology. The random effect was not significant (p value 1.000). Therefore, the Intraclass Correlation Coefficient (ICC) was 98.65% (CI 100.00–96.99%). Conclusion . CBCT is an accurate technique to measure even thin bone structures in the vicinity of titanium implants.